2012
DOI: 10.5435/jaaos-20-05-273
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Compromised Fracture Healing

Abstract: No standard criteria exist for diagnosing fracture nonunion, and studies suggest that assessment of fracture healing varies among orthopaedic surgeons. This variability can be problematic in both clinical and orthopaedic trauma research settings. An understanding of risk factors for nonunion and of diagnostic tests used to assess fracture healing can facilitate a systematic approach to evaluation and management. Risk factors for nonunion include medical comorbidities, age, and the characteristics of the injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
168
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(185 citation statements)
references
References 38 publications
1
168
0
8
Order By: Relevance
“…3 The risk of nonunion is related to the severity of injury resulting in fracture, 4 and many randomized clinical trials 5 have shown that variations in nonunion rates are associated with different surgical treatments. However, progression to nonunion is not fully explained by these factors alone.…”
mentioning
confidence: 99%
“…3 The risk of nonunion is related to the severity of injury resulting in fracture, 4 and many randomized clinical trials 5 have shown that variations in nonunion rates are associated with different surgical treatments. However, progression to nonunion is not fully explained by these factors alone.…”
mentioning
confidence: 99%
“…Several studies have elucidated risk factors associated with a failure to achieve union after fracture. [1][2][3][4][5] Factors precluding healing can be grouped into those associated with mechanical instability or those associated with poor fracture biology. 1 An unstable fixation construct leads to potential shearing forces at the fracture site which limits both primary and secondary bone healing.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Factors precluding healing can be grouped into those associated with mechanical instability or those associated with poor fracture biology. 1 An unstable fixation construct leads to potential shearing forces at the fracture site which limits both primary and secondary bone healing. 6 Biologic factors are sometimes implicated and include complex fracture patterns, bony comminution, interfragmentary gap, bone loss, poor soft tissue coverage, and vascular deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…FDA (United States Food and Drug Administration)'ya göre, bir kırığa kaynamama denilebilmesi için yaralanmadan sonraki 9. ayda hala tam iyileşme olmaması ya da son üç aylık takiplerinde iyileşmede herhangi bir ilerlemenin olmaması gerekir. [50] Kemiğin ne kadarlık bir kısmının yaralandığı, kırığın şekli, bölgesi ve kırığa ek yaralanmalar, hastanın yaşı, ek hastalıkları, kullandığı ilaçlar, sigara alışkanlığı göz önünde bulundurularak, kaynamanın buna göre değerlendirilmesi gerekmektedir. [51] Kaynamama Tipleri a. Hipertrofik kaynamama: Kanlanmanın yeterli olduğu kırıklarda fragmanlar arasındaki fazla harekete bağlı belirgin kallus oluşumu, doku farklılaş-masında yetersizlikle karakterize kaynamamadır.…”
Section: B2 Eksternal Fiksatörlerunclassified